Педагогіка партнерства як чинник психолого-педагогічної підтримки батьків у професійному самовизначенні старшокласників - Гунчак, Олександр; Равлюк, Тетяна (My University, 2026)
The relevance of the study is caused by the systemic transformations in Ukrainian education, which require a rethinking of the interaction between school and family in the process of students’ career guidance. In contemporary conditions, the choice of a profession by senior school students is accompanied by a high level of parental anxiety, which highlights the need to develop effective models of psychological and pedagogical support for parents based on the principles of partnership. The aim of the article is to provide a theoretical substantiation and to reveal the content of partnership-based interaction between teachers and parents as a key factor in supporting students’ professional self-determination. To achieve this aim, a range of theoretical methods was employed, including: analysis of the regulatory framework of the New Ukrainian School and scientific literature; terminological clarification of new socio-professional roles of teachers; and systematic generalization to substantiate practical tools for career guidance activities. The content of the study reveals a shift in the paradigm of career guidance from directive informing to a humanistic, subject–subject interaction among participants in the educational process. Particular attention is paid to the transformation of teachers’ functions, who, within a partnership system with the family, master new professional roles aimed at supporting adolescents in making conscious career choices. In particular, the role of the teacher-facilitator is substantiated as one who creates a safe communicative environment; the teacher-tutor is defined as a personal navigator of the family’s individual educational trajectory; and the teacher-coach is characterized as an activator of family resources for making informed decisions. The prospects of implementing a system of interactive methods for the realization of partnership pedagogy is argued, including discussion panels (World Café), the “Educational Breakthrough Map” technology, SMART planning, and gamification. The scientific novelty of the study lies in substantiating the content of new teacher roles (facilitator, tutor, coach) as subjects providing support to parents, which contributes to their transformation from passive observers into active partners.
Keywords: pedagogical interaction, pedagogy of partnership, psychological and pedagogical support, professional self-determination, teacher-facilitator, teacher-tutor, teacher-coach, interactive methods.